2020
DOI: 10.1021/acssuschemeng.9b06080
|View full text |Cite
|
Sign up to set email alerts
|

Body Temperature-Triggered Shape-Memory Effect via Toughening Sustainable Poly(propylene carbonate) with Thermoplastic Polyurethane: toward Potential Application of Biomedical Stents

Abstract: Shape-memory polymeric materials triggered by body temperature were fabricated via toughening sustainable poly­(propylene carbonate) (PPC) with thermoplastic polyurethane (TPU). With an addition of TPU through melt blending, the ductility of PPC was dramatically enhanced, leading to the increase of shape recoverability but a deterioration of shape fixity. Remarkably, the blend containing 50 wt % TPU (PT50) presented the optimal shape-memory effect (SME) with balanced shape recovery and shape fixation performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…PPC has a wide range of applications, and due to its widely exhibited properties, it is now widely used in film-like materials, cushioning foams [ 118 ], adhesives, medical materials [ 119 ], battery materials [ 120 ], sheets, plastic modification aids, toughening agents, coatings/inks and many other fields. It has the potential to replace PE and PP in the preparation of disposable materials [ 121 ].…”
Section: Applications Of Ppcmentioning
confidence: 99%
“…PPC has a wide range of applications, and due to its widely exhibited properties, it is now widely used in film-like materials, cushioning foams [ 118 ], adhesives, medical materials [ 119 ], battery materials [ 120 ], sheets, plastic modification aids, toughening agents, coatings/inks and many other fields. It has the potential to replace PE and PP in the preparation of disposable materials [ 121 ].…”
Section: Applications Of Ppcmentioning
confidence: 99%
“…For instance, there are commercially available monomers for the synthesis of such bio-based polyols as succinic acid, sebacic acid, 2,5-furanodicarboxylic, ethylene glycol, 1,3-propanodiol, and 1,4-butanodiol. In the research literature, we can find out information about the use of such bio-based polyols as poly(trimethylene succinate)s [ 4 ], poly(trimethylene glycol)s [ 2 , 14 ], and poly(propylene carbonate) [ 15 ] for the preparation of TPUs. Moreover, there are a lot of work that describe results of using polyols based on vegetable oils such as rapeseed oil [ 16 ], seed oil [ 17 ], and soybean oil [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microphase separation structure of TPU endows thermoplastic polymers with excellent shape-memory properties while the hard segments of TPU are used as a permanent phase for shapememory properties. 32 To endow the material with fast selfhealing properties, a low-melting-temperature healing agent is mixed into the TPU system. After heating, the healing agent melts and flows into the damaged area.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is reported that multifunctional materials with shape-memory and self-healing properties based on thermoplastic polymers have been synthesized by blending thermoplastic polyurethane (TPU) with a healing agent. The microphase separation structure of TPU endows thermoplastic polymers with excellent shape-memory properties while the hard segments of TPU are used as a permanent phase for shape-memory properties . To endow the material with fast self-healing properties, a low-melting-temperature healing agent is mixed into the TPU system.…”
Section: Introductionmentioning
confidence: 99%